The Implementation of Character Education at Ar-Rahmah Integrated Islamic Elementary School of Makassar - Syahruddin, Syahruddin (Al-Ulum, 2015)
The implementation of character education as reflected in QS Luqman: 12-19 at the Ar-Rahmah Integrated Islamic Elementary School of Makassar learners is integrated into the whole school programs. Those programs namely: integrated in every subjects, the development of school culture, extra-curricular activities, cooperation with learnersâ parents, the control card (yaumian card) and means of communication via group in website. The impact of character education on learnersâ attitude and behavior can be identified from their daily attitude and behavior like being discipline, praying dhuha, praying dhuhur in congregation, keeping the school environment clean, keeping mutual appreciating among their friends, being responsible towards the task assigned by the teachers, maintaining order in the learning process, and asking for permission when they want to get out.-----Implementasi pendidikan karakter yang tercermin dalam QS Luqman ayat: 12 â 19Â  pada peserta didik di Sekolah Dasar Islam Terpadu Ar Rahma Makassar di integrasikan ke dalam seluruh program sekolah. Program tersebut, antara lain: terintegrasi dalam setiap mata pelajaran, melalui pengembangan budaya sekolah, kegiatan ekstrakurikuler, kerjasama antara orang tua peserta didik, menggunakan kartu kontrol (kartu yaumian) dan sarana komunikasi lewat group in website. Dampak pendidikan karakter pada peserta didik terlihat dari perilaku setiap hari: disiplin, melaksanakan shalat duha,Â  shalat duhur berjamaah, menjaga kebersihan lingkungan sekolah saling menghargai temannya, tanggung jawab terhadap tugas yang diberikan oleh guru, menjaga ketertiban dalam belajar, dan minta izin jika ingin keluar.